KESINONIMAN VERBA ORIRU DALAM BAHASA JEPANG (Kajian Semantik) - Maharani Patria Ratna (IZUMI, 2013)
Abstract Oriruin Japanesewhichmeans ''turun ''in Indonesian has an unique characteristicsdue to it has twokanjis, (降りる)and(下りる). Based on its semantic meaning, oriru verb of A could be substituted for oriru verb of B in a sentence which describes a down movement of vehicle. Besides, oriru verb of A isused to describe the down motion in a change of venue, while下りる is merely used to describethe down motion. Keywords : down, 降りるand下りる, synonyms, differences, place.